Growing choroidal osteoma: Treated by proton beam radiation - Ahad Sedaghat; Mary E. Aronow; Arun D. Singh (Taiwan Journal of Ophthalmology)
Choroidal osteoma is a rare, slow-growing intraocular osseous tumor. Limited information is available regarding the management of tumors growing toward the fovea. In this study, we present two cases of growing choroidal osteoma that were successfully treated with proton beam radiation therapy. In one case, tumor growth toward the fovea in a 12-year-old female was treated with proton beam radiation as the primary intervention. In the other, proton beam radiation was used after photodynamic therapy failed to control tumor growth in a 16-year-old female with choroidal osteoma. Both cases demonstrated sustained tumor growth cessation for 42 and 38 months, respectively. Low-dose proton beam radiation appears to be an effective treatment option to halt tumor growth and preserve vision, though long-term follow-up is essential.